2023
DOI: 10.1002/pbc.30243
|View full text |Cite
|
Sign up to set email alerts
|

Massage therapy for children, adolescents, and young adults: Clinical delivery and effectiveness in hematology and oncology

Abstract: Background Children, adolescents, and young adults with hematologic and/or oncologic conditions experience multiple, significant symptoms (e.g., pain, stress, and anxiety), which may be addressed by nonpharmacologic approaches such as massage therapy (MT). The purpose of this study was to describe the clinical delivery of MT provided by a certified pediatric massage therapist and assess effectiveness in two patient groups: those with sickle cell disease (SCD) or hematologic and/or oncologic conditions excludin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Patients’ IHM survey responses indicated that music (55.6%), art (51.9%), and massage therapy (38.9%) programs were of interest to help with pain. These findings align with previous studies demonstrating the benefit of these modalities for addressing acute pain, stress, and anxiety 9–12 . Indeed, many of the patients surveyed may have participated in these interventions during previous hospital admissions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients’ IHM survey responses indicated that music (55.6%), art (51.9%), and massage therapy (38.9%) programs were of interest to help with pain. These findings align with previous studies demonstrating the benefit of these modalities for addressing acute pain, stress, and anxiety 9–12 . Indeed, many of the patients surveyed may have participated in these interventions during previous hospital admissions.…”
Section: Discussionsupporting
confidence: 89%
“…Several clinical trials have supported the benefits of IHM modalities including acupuncture 7 and massage therapy 8 for addressing acute pain among youth and adults with SCD, and music therapy for addressing acute 9 and chronic pain 10 among adults with SCD. Additionally, recent observational studies have demonstrated the clinical effectiveness of massage therapy 11 and music therapy 12 among pediatric and adult patients with SCD, respectively. With accumulating data supporting the benefits of these modalities, 13 appropriate screening and triage are needed to best optimize delivery of these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on pediatric massage with cancer and sickle cell patients, 3015 sessions were provided for 243 patients (approximately 12 sessions per patient) (mean age=12) [29]. All of the patients reported less pain, stress, and anxiety.…”
Section: Decreased Symptoms In Cancer and Sickle Cell Rodgers-melnickmentioning
confidence: 99%
“…In accordance with prior established tenets of whole health, UHCWH partners with UH providers, departments, and institutes to provide IHM modalities and empower patients in managing health and wellbeing while centering patient goals [45]. In efforts to meet the growing demand for comprehensive strategies to manage a wide variety of health concerns, UHCWH services are integrated into the UH health system across primary care, multispecialty outpatient care [46], hematology/oncology [47][48][49], fertility, rehabilitation, and orthopedic divisions spanning a central academic medical center [50] and eight community hospitals [51].…”
Section: Settingmentioning
confidence: 99%
“…2.4.1 Questionnaires. The numeric rating scale (NRS) is commonly used for measuring pain, stress, and anxiety in clinical practice [52][53][54] and research [44,48,51], with demonstrated validity across these constructs. Owing to its simplicity, ease of use across populations, focus on symptoms in the present moment, and generalizability across various age and education levels [52], the NRS was selected as the instrument of choice in the present study.…”
Section: Data Collectionmentioning
confidence: 99%